Noninvasive ventilation for severe legionella pneumonia - (:unkn) unknown (Springer-Verlag Wien, 2014)
Legionnaires’ disease was first recognized at the 1976 American Legion Convention in Philadelphia, in which 182 American Legionnaires contracted pneumonia and 34 individuals died [1]. Investigators from the Centers for Disease Control and Prevention (CDC) subseqently identified the causative agent as an aerobic Gram-negative bacterium and named it Legionella pneumophila. During the last three and a half decades, L. pneumophila has become widely recognized as a cause of community-acquired pneumonia (CAP) in patients who required intensive care unit (ICU) admission. In many studies, the clinical manifestations for legionnaires’ disease were more severe and the mortality was higher when compared with pneumonias of other etiologies. This may be due to a delay in diagnosis and suboptimal antibiotic therapy rather than enhanced virulence of L. pneumophila. Strains of L. pneumophila differ in virulence. L. pneumophila causes more severe disease than other bacterial pathogens associated with acquired pneumonia. The mortality associated with Legionnaires’ disease is notably higher than that the other atypical pneumonias in which L. pneumophila is included (Chlamydia pneumoniae and Mycoplasma pneumoniae are the others). Mortality is similar to that of bacteremic pneumococcal pneumonia. © Springer-Verlag Wien 2014.
Keywords: Pneumonia